2021
DOI: 10.1038/s42003-021-01727-9
|View full text |Cite
|
Sign up to set email alerts
|

Depth-dependent parental effects create invisible barriers to coral dispersal

Abstract: Historically, marine populations were considered to be interconnected across large geographic regions due to the lack of apparent physical barriers to dispersal, coupled with a potentially widely dispersive pelagic larval stage. Recent studies, however, are providing increasing evidence of small-scale genetic segregation of populations across habitats and depths, separated in some cases by only a few dozen meters. Here, we performed a series of ex-situ and in-situ experiments using coral larvae of three broodi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
20
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(26 citation statements)
references
References 103 publications
4
20
2
Order By: Relevance
“…This result is in agreement with that of Bongaerts et al (2017), where shallow‐to‐deep introgression in Agaricia fragilis is inferred from asymmetry in the private allele distribution, and Prada and Hellberg (2021), where asymmetrical introgression in the Caribbean octocoral Eunicea flexuosa is shown to favour the shallow‐to‐deep to direction. Moreover, it also aligns with recent experimental evidence from two Stylophora species and a brooding octocoral demonstrating that shallow‐origin larvae exhibit lower settlement specificity across shallow and deep conditions compared with mesophotic‐origin larvae (Shlesinger & Loya, 2021).…”
Section: Discussionsupporting
confidence: 87%
“…This result is in agreement with that of Bongaerts et al (2017), where shallow‐to‐deep introgression in Agaricia fragilis is inferred from asymmetry in the private allele distribution, and Prada and Hellberg (2021), where asymmetrical introgression in the Caribbean octocoral Eunicea flexuosa is shown to favour the shallow‐to‐deep to direction. Moreover, it also aligns with recent experimental evidence from two Stylophora species and a brooding octocoral demonstrating that shallow‐origin larvae exhibit lower settlement specificity across shallow and deep conditions compared with mesophotic‐origin larvae (Shlesinger & Loya, 2021).…”
Section: Discussionsupporting
confidence: 87%
“…Importantly, the higher settlement success of mesophotic larvae under shallow light conditions compared to shallow larvae under mesophotic light conditions suggests that recruitment may preferentially occur up the slope (mesophotic to shallow) rather than down the slope (shallow to mesophotic). These results oppose previous observations of asymmetric gene flow (Prada and Hellberg, 2013;Serrano et al, 2014;Bongaerts et al, 2017) and larval settlement patterns (Shlesinger and Loya, 2021) occurring from shallow to deeper reefs. Nevertheless, the higher reproductive success observed for mesophotic corals in the Western Atlantic (Holstein et al, 2015; and subsequent larval effective recruitment found in the present study suggest that mesophotic reefs likely represent a significant source of propagules across the depth gradient and may aid in the recovery of degraded shallow reefs in Bermuda.…”
Section: Discussioncontrasting
confidence: 99%
“…Furthermore, shallow reefs in Bermuda are more likely impacted by anthropogenic activities (Smith et al, 2013), which can also reduce the fitness of shallow adult colonies. Parental effects have been indicated as major factors limiting coral larval dispersal across depths as larvae may be adapted to the conditions experienced by their parent (Shlesinger and Loya, 2021), however, our findings show that offspring plasticity also plays a crucial role in shaping coral capacity to colonize differing environments. Yet, the density of adult P. astreoides colonies on shallow and mesophotic reefs in Bermuda does not reflect a pattern of increased recruitment to mesophotic depth, as adult colony frequency is documented to decrease with increasing depth (Fricke and Meischner, 1985).…”
Section: Discussionmentioning
confidence: 64%
See 1 more Smart Citation
“…In mesophotic reefs, in situ surveys of recruitment patterns have mostly been limited to the northern Red Sea and Western Australia, where artificial settlement tiles have been employed to count new coral recruits (Turner et al, 2018;Kramer et al, 2019;Shlesinger and Loya, 2021). Several studies have evaluated in situ coral recruitment patterns in the shallow reefs of Eilat and Bermuda through visual underwater identification of coral recruits on settlement tiles or on the natural substrate (Smith, 1992;Glassom et al, 2004;Abelson et al, 2005;Glassom and Chadwick, 2006;Martinez and Abelson, 2013;Shlesinger and Loya, 2016;Guerrini et al, 2020).…”
Section: Discussionmentioning
confidence: 99%